Predicting self-care practices and glycaemic control using health belief model (HBM) in patients with insulin-treated diabetes in Malaysia - Aris, Aishairma (2016)
Background: The practice of diabetes self-care plays an important role in glycaemic control. However, not all patients with insulin-treated diabetes engage in their self-care activities. Although there is evidence that self-care practices in patients with insulin-treated diabetes can be understood and predicted by health beliefs proposed by Health Belief Model (HBM), little is known about adult patients due to several methodological weaknesses of previous studies. Furthermore, knowledge is lacking about adults with insulin-treated diabetes in Malaysia.